PENERAPAN COST REDUCTION STRATEGIES DI MASA PANDEMI COVID-19 PADA USAHA KECIL MENENGAH (UMKM) KOTA BOGOR (Studi pada Anggota UMKM di Komunitas Kefir Bogor) - Sri Hastuti (POLITEKNIK LP3I JAKARTA, 2021)
This research purpose to know the application of Cost Reduction Strategies on Micro Small and Medium Enterprises (MSME). Cost reduction strategies have the meaning of